PENGARUH MEDIA SOSIAL TERHADAP KOSAKATA BAHASA INDONESIA DI KALANGAN GENERASI MUDA: SEBUAH STUDI LITERATUR - Moh. Anugrah Pakaya; Yusniati N. Sabata; Ita Rosvita; Sitti Hardianti (Jurnal Bastra (Bahasa dan Sastra), 2026)
Social media has become a massive communication space for young people, significantly influencing the development of Indonesian vocabulary. This study examines the impact of social media on Indonesian vocabulary, particularly the rise of slang, loanwords, and the decline of standard language use. Using a literature review method, this research analyzed scholarly articles, books, and official documents relevant to the topic. The findings show that social media accelerates the spread of new vocabulary, both slang and borrowed words, which on one hand reflects the creativity and adaptability of the Indonesian language, but on the other hand poses challenges to the preservation of standard usage. This phenomenon also has the potential to weaken formal academic competence, particularly scientific writing skills among younger generations. The study highlights the importance of digital literacy as a strategy to balance linguistic creativity with adherence to language norms.